EFEKTIVITAS PENGGUNAAN APLIKASI QUIZIZZ SEBAGAI KUIS INTERAKTIF TERHADAP KEMAMPUAN KOGNITIF DAN MOTIVASI BELAJAR MAHASISWA - Yusina Fadla Ilmi (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
This study aims to determine the effectiveness of using the Quizizz Application as an interactive quiz on students' cognitive abilities and learning motivation. This research approach is a descriptive quantitative approach. This type of research is quasi-experimental, with a one group pretest-posttest design. The sampling technique used is the total sampling technique. Data collection techniques using tests and non-tests were carried out using 35 multiple choice questions to determine students' cognitive abilities. Data analysis techniques using normality test, homogeneity test and hypothesis testing. The results showed that the quizizz application was effectively used as a learning evaluation tool for students' cognitive abilities and learning motivation.